STUDI KEPEDULIAN LAKI-LAKI TERHADAP KESEHATAN REPRODUKSI PEREMPUAN DI KAMPUNG RANJENG - Rahmawati Rahmawati; Rina Yulianti (Universitas Sultan Ageng Tirtayasa, 2010)
Improved access to health services for women of course originated from the family / home, where husband / male has a big role. Understanding and involvement of husbands in providing information about women's reproductive health is one manifestation of attention and affection of a husband to his wife. This study tries to see how the concerns of men about women's reproductive health Ranjeng Village. Is a qualitative research method in this study with key informants were men and his wife as the Kampung Ranjeng secondary informants. This study found the results of research that understanding husband / men about reproductive health of women and various kinds of diseases that can affect female reproductive organs, both local and immigrant population is still low. This is influenced by economic factors, education, culture. Concern men in Kampung Ranjeng on reproductive health is influenced by economic considerations and more towards the use of contraceptives.